Antioxidant and insulin-like properties of extracts from wheat grains fermented by selected indigenous ganoderma spp. / Sarasvathy Subramaniam - Subramaniam, Sarasvathy (2013)
Ganoderma are cosmopolitan wood decaying white rot basidiomycete fungi,which have been used for centuries for medicinal purposes, particularly in China, Japan and Korea. It is believed to possess many health benefits and has been reported to be effective against various diseases by virtue of their antioxidant potential. In the present study, solid-substrate fermentation of wheat grains with indigenous Ganoderma spp. selected based on ethnomycological knowledge was carried out. The species included Ganoderma australe (Fr.) Pat. (KUM60813), Ganoderma neo-japonicum Imazeki(KUM61076) and Ganoderma lucidum (Fr.) Karst. (VITA GL) (a commercial strain). Antioxidant activities of the crude aqueous and ethanol extracts of the unfermented and fermented wheat grains were investigated by the ferric reducing antioxidant power (FRAP), 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity, diphenyl-1-picryl-hydrazyl (DPPH) free radical scavenging ability and lipid peroxidation assays. Among the six mycelia extracts tested, the ethanol extract from wheat fermented with KUM61076 mycelia showed the most potent antioxidant activities whereas, the ethanol extract of wheat grains fermented with KUM60813 mycelia had good potential to protect palm oil (food grade) against oxidation. Total phenol content (TPC) in the ethanol extracts were higher than that in the aqueous extracts. The antioxidant activities of the mycelia extracts had a positive correlation with their polyphenol contents. These phenolic compounds may play a vital role in the antioxidant activities of the selected Ganoderma spp. The present study also evaluated the insulin-like properties of extracts of unfermented and fermented wheat grains through lipogenic, lipolytic and adipokine expression. 3T3-L1 adipocytes treated with ethanol extract of wheat grains fermented with KUM61076 mycelia, significantly stimulated lipogenesis (in the absence of insulin) and exerted relatively mild antiiii adrenaline induced lipolytic activities. In general, the expressions of target genes such as adiponectin, peroxisome proliferator-activated receptor gamma (PPARγ), glucose transporter 4 (GLUT4) and hormone sensitive lipase (HSL) were up-regulated by the ethanol extract of wheat grains fermented with Ganoderma spp. mycelia. However, both the aqueous and ethanol extracts of unfermented and fermented wheat grains demonstrated a dose-dependent inhibition of preadipocyte differentiation and reduced the expression level of adiponectin in adipocytes when the cells were subjected to oxidative stress. In conclusion, these results suggest that wheat grains fermented with Ganoderma spp. especially KUM60813 and KUM61076 have good antioxidant and insulin-like properties which may potentially serve as a therapeutic agent in the management of diabetes. To our knowledge this is the first report on antioxidant and insulin-like properties of extracts from wheat grains fermented by Ganoderma spp. mycelia.